2015
DOI: 10.3390/ma8052243
|View full text |Cite
|
Sign up to set email alerts
|

Water Absorption Behavior of Hemp Hurds Composites

Abstract: In this paper, water sorption behavior of 28 days hardened composites based on hemp hurds and inorganic binder was studied. Two kinds of absorption tests on dried cube specimens in deionized water bath at laboratory temperature were performed. Short-term (after one hour water immersion) and long-term (up to 180 days) water absorption tests were carried out to study their durability. Short-term water sorption behavior of original hemp hurds composites depends on mean particle length of hemp and on binder nature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 33 publications
1
36
0
1
Order By: Relevance
“…Different treatments on sisal fibers reduced the diffusion coefficient and similar to the ONPF composites, the diffusion coefficient increased with the fiber content and decreased when fiber treatments were applied [34]. This was also noticed in other studies that studied the relation between water sorption behavior and fiber chemical composition [58].…”
supporting
confidence: 77%
“…Different treatments on sisal fibers reduced the diffusion coefficient and similar to the ONPF composites, the diffusion coefficient increased with the fiber content and decreased when fiber treatments were applied [34]. This was also noticed in other studies that studied the relation between water sorption behavior and fiber chemical composition [58].…”
supporting
confidence: 77%
“…The use of hemp hurd as a filler in polymer matrix composites is not entirely new and previous research has shown that properties comparable to the ones obtained using wood flour as a filler (Cigasova et al, n.d.;Khan et al, 2015;Kidalova et al, 2015;Stevulova et al, 2015) can be achieved. As shown in Table 1, the chemical composition of hemp hurd is comparable to wood four.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the jute fabric-reinforced composites absorbed water very rapidly at the initial stage, and later a saturation level was attained without any further increase in water sorption. It is known that factors such as porosity content and fabric-matrix adhesion are responsible for the moisture absorption behavior of natural fabric composites (Stevulova et al 2015). In these cases, the hydrophilicity of jute fabric, voids contents, and fabric-matrix adhesion might affect the moisture uptake of the composites.…”
Section: Water Absorption Propertiesmentioning
confidence: 99%